Development of a double model slab tracking control system for the continuous reheating furnace. (October 2017) - Yi, Zhi; Su, Zhenggang; Li, Guojun; Yang, Qiangda; Zhang, Weijun
Highlights: A double model slab tracking system for continuous reheating furnace is developed. The heating process in the hearth is described by the ternary model. The temperature fields of slabs is calculated by the total exchange factor model. The total exchange factors are weighted by the ternary model and the experiment data. The furnace temperature is simulated by the ternary model. Abstract: In the automatic control system of a continuous reheating furnace, a reasonable and accurate mathematical model, whose core tasks are tracking and calculating the temperature fields of slabs, is important for improving product quality and reducing energy consumption. By combining the characteristics of the mechanism model and the semi-empirical model, the double model slab tracking (DMST) control system for a walking beam reheating furnace of Baosteel is developed. The heating processes of two trailing thermocouple experiments are simulated by the system. The average deviations of slab temperatures between two experimental and simulation results are 26.9 °C and 25.0 °C, respectively. The maximum deviations are 71.3 °C and 79.4 °C respectively, which means that both maximum relative deviations are less than 8%. Therefore, the DMST control system could satisfy the requirements of various productions. Thereafter the productive process is tracked and simulated by the DMST control system for one month. Taking the surface temperature of the discharged slab as a comparative object, the proportion of slabs whose simulation deviations are less than 20 °C is more than 95%, which shows that the DMST control system has excellent accuracy.